2022
DOI: 10.3390/brainsci12050536
|View full text |Cite
|
Sign up to set email alerts
|

Role of SARS-CoV-2 in Modifying Neurodegenerative Processes in Parkinson’s Disease: A Narrative Review

Abstract: The COVID-19 pandemic, caused by SARS-CoV-2, continues to impact global health regarding both morbidity and mortality. Although SARS-CoV-2 primarily causes acute respiratory distress syndrome (ARDS), the virus interacts with and influences other organs and tissues, including blood vessel endothelium, heart, gastrointestinal tract, and brain. We are learning much about the pathophysiology of SARS-CoV-2 infection; however, we are just beginning to study and understand the long-term and chronic health consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 215 publications
0
7
0
Order By: Relevance
“…SARS-CoV-2 seems to interact with and manipulate mitochondria in order to hijack and evade mitochondria-mediated immune response for its own replication and survival [ 179 , 180 ]. In this effort, SARS-CoV-2 may induce mitochondrial impairment [ 181 , 182 ], mitochondria-mediated oxidative stress, and mitochondrial damage through mitochondrial membrane depolarization, mitochondrial permeability transition pore opening, and enhanced ROS release [ 183 , 184 , 185 ]. Furthermore, the virus prevents mitophagy by blocking the binding of p62 and microtubule-associated protein 1A/1B-light chain 3 (LC3), thereby hindering viral RNA breakdown [ 185 ].…”
Section: Sars-cov-2 Infection and Pd Overlapsmentioning
confidence: 99%
“…SARS-CoV-2 seems to interact with and manipulate mitochondria in order to hijack and evade mitochondria-mediated immune response for its own replication and survival [ 179 , 180 ]. In this effort, SARS-CoV-2 may induce mitochondrial impairment [ 181 , 182 ], mitochondria-mediated oxidative stress, and mitochondrial damage through mitochondrial membrane depolarization, mitochondrial permeability transition pore opening, and enhanced ROS release [ 183 , 184 , 185 ]. Furthermore, the virus prevents mitophagy by blocking the binding of p62 and microtubule-associated protein 1A/1B-light chain 3 (LC3), thereby hindering viral RNA breakdown [ 185 ].…”
Section: Sars-cov-2 Infection and Pd Overlapsmentioning
confidence: 99%
“…It has been reported that SARS-CoV-2 is able to enter the brain and trigger the release of inflammatory mediators [ 34 ] that are known to play a role in neurodegeneration. SARS-CoV-2 can enter the brain by invading the olfactory bulb, by axonal transport from peripheral nerves, and by hematogenous pathways through the BBB [ 35 ]. SARS-CoV-2 could bind to ACE2 receptors on dopaminergic neurons, altering the rate of accumulation of misfolded α-synuclein, and promoting mitochondria stress, autophagy, and apoptosis [ 35 , 36 ].…”
Section: Covid-19 and Pdmentioning
confidence: 99%
“…SARS-CoV-2 can enter the brain by invading the olfactory bulb, by axonal transport from peripheral nerves, and by hematogenous pathways through the BBB [ 35 ]. SARS-CoV-2 could bind to ACE2 receptors on dopaminergic neurons, altering the rate of accumulation of misfolded α-synuclein, and promoting mitochondria stress, autophagy, and apoptosis [ 35 , 36 ]. Apart from the direct invasion of SARS-CoV-2 into the CNS, post-infection immune-mediated process also plays an important role in the development of PD [ 37 ].…”
Section: Covid-19 and Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential pathophysiological or etiological impact of SARS-CoV-2 on PD is discussed in four review articles. Morowitz et al present a narrative review about the role of SARS-CoV-2 in modifying neurodegenerative processes in PD [ 5 ]. Drelich-Zbroja attempt to collate the existing scientific evidence regarding the possible role of SARS-CoV-2 in the pathophysiology of PD [ 6 ].…”
mentioning
confidence: 99%